The Esmeraldas Canyon: A Helpful Marker of the Pliocene‐Pleistocene Tectonic Deformation of the North Ecuador‐Southwest Colombia Convergent Margin. Issue 8 (24th August 2019) - Collot, J.‐Y.; Ratzov, G.; Silva, P.; Proust, J.‐N.; Migeon, S.; Hernandez, M.‐J.; Michaud, F.; Pazmino, A.; Barba Castillo, D.; Alvarado, A.; Khurama, S.
Abstract: Deciphering the migration pattern of the Esmeraldas submarine Canyon (EC) and its history of cut‐and‐fill allows constraining the Pliocene‐Pleistocene tectonic evolution of the Ecuador‐Colombia convergent margin. Swath bathymetry, multichannel seismic reflection, and chronological data show that the EC is a 143‐km‐long, shelf‐incising, river‐connected canyon that started incising slope apron deposits in the Manglares fore‐arc basin 5.3 Ma ago. The EC inception appears contemporaneous with the subduction of the Carnegie Ridge that is believed to have initiated 5–6 Myr ago and is considered an indirect cause of the EC formation. During its two‐stage left‐lateral migration, the EC upper‐half scoured deep incisions providing evidences for uplift episodes in the Manglares Basin that are correlated with mid‐Pliocene and Pleistocene regional tectonic events. Glacioeustatic variations contributed significantly to shape the EC and its upslope tributaries by increasing the rate of canyon incision during rapid sea level falls. Faults, folds, and diapirs have structurally controlled the location of the EC and of its tributary canyons, including the Ancon Canyon, which served as the main spillway of the Manglares Basin prior to be cut from its source 170 kyr ago by the growth of a fault‐related anticline. The margin wedge that hosts the EC is highly unstable as it is cut by active faults and shaken by large subduction earthquakes. Several mass transport deposits have dammed the EC, one of them between > 65 and 37 kyr causing an impoverishment of detrital material in the trench sedimentation and a possible interruption of the paleoseismological record. Key Points: The Esmeraldas Canyon (EC) started incising the Manglares Basin 5.3 Ma ago contemporarily with the Carnegie Ridge subduction initiation The EC migration and incisions reveal Plio‐Quaternary fore‐arc uplift episodes and the conspicuous influence of glacioeustatic variations The Ancon Canyon, the main spillway of the Manglares fore‐arc basin, was abandoned 170 kyr ago favoring the basin infill